A perspectiva temporal no projeto de interfaces gráficas - Lebtag, Paulo Lucas Araújo (2021)
This work discusses, from the perspective of merleaupontian phenomenology, about the temporal dimension in the design tools of graphic interfaces. The discussion is about the definition of what is the temporal perspective according to the concepts of the phenomenologist Maurice Merleau-Ponty. It exposes what graphic interfaces are and their relationship with contemporary society. It presents what is the design of graphical interfaces and its relationship with design tools. It is analyzed the tools present in the Design Toolkit of the Universitat Oberta de Catalunya (2020), discussing the temporal perspective in each of the tools. The tools that have a temporal bias are highlighted and structured in an instruction on how to develop a project from a temporal perspective. It is concluded that the study of the temporal perspective enriches the designer and makes it possible to problematize the interfaces in a more adequate way to the liquid contexts of contemporaneity.